2017
DOI: 10.1016/j.mce.2017.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic regulation of spermatogonial differentiation in zebrafish (Danio rerio) by Igf3 and Amh

Abstract: Fsh-mediated regulation of zebrafish spermatogenesis includes modulating the expression of testicular growth factors. Here, we study if and how two Sertoli cell-derived Fsh-responsive growth factors, anti-Müllerian hormone (Amh; inhibiting steroidogenesis and germ cell differentiation) and insulin-like growth factor 3 (Igf3; stimulating germ cell differentiation), cooperate in regulating spermatogonial development. In dose response and time course experiments with primary testis tissue cultures, Fsh up-regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 88 publications
1
47
1
Order By: Relevance
“…Asterisks indicate significant differences (*P < 0.05) between basal and experimental group. D Safian et al 239:3 Journal of Endocrinology that zebrafish testis tissue also expresses several noncanonical Wnt receptors (Crespo et al 2016, Morais et al 2017. However, no information is available on the question which receptor specifically responds to WNT5a in mice or zebrafish testis tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Asterisks indicate significant differences (*P < 0.05) between basal and experimental group. D Safian et al 239:3 Journal of Endocrinology that zebrafish testis tissue also expresses several noncanonical Wnt receptors (Crespo et al 2016, Morais et al 2017. However, no information is available on the question which receptor specifically responds to WNT5a in mice or zebrafish testis tissue.…”
Section: Discussionmentioning
confidence: 99%
“…However, zebrafish Fsh also stimulates spermatogonial differentiation in an androgen-independent manner, for example by stimulating the release of Igf3 mainly from SCs (Nóbrega et al 2015) and of Insl3 from LCs (Assis et al 2016. Moreover, Fsh suppresses the production of the SC-derived anti-Müllerian hormone (Amh) (Skaar et al 2011), which would otherwise exert inhibitory effects on spermatogenesis (Morais et al 2017). Crespo et al (2016) identified ~200 testicular transcripts responding to zebrafish Fsh in an androgen-independent manner, including genes belonging to the Wnt signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, cortisol significantly increased the transcript level of amh (anti-Müllerian hormone) after 7 days of culture. Amh, a member of transforming growth factor β, is expressed in Sertoli cells [77,80], and exerts an important role in spermatogonial proliferation and differentiation, as reported in zebrafish and other fish species [80]. Moreover, studies have shown that Amh inhibits spermatogonial proliferation and differentiation in zebrafish testis [66,77,81].…”
Section: Discussionmentioning
confidence: 88%
“…We also examined whether cortisol-induced spermatogonial proliferation and differentiation could be mediated through a stimulatory growth factor, Igf3 (Insulin-like growth factor 3). Igf3 is a Sertoli cell derived growth factor that promotes spermatogonial proliferation and differentiation in the zebrafish testes [44,[77][78][79]. Cortisol treatment did not affect igf3 transcript level in the zebrafish testis.…”
Section: Discussionmentioning
confidence: 95%